2011
DOI: 10.1007/s13304-011-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of tailored D2 lymph node dissection after R0 surgery for gastric cancer

Abstract: Implementation of extended lymph node dissection for gastric cancer in western non-specialized centers through tailoring its extent upon disease stage and patient comorbidities was suggested as a wise policy to reduce morbidity and mortality rates, albeit with a potential for undertreatment in elderly and/or comorbid patients. Current definition of R(0) resection for gastric cancer lacks consideration of treatment-related variables such as extended lymph node dissection. Few studies to date have tried to fill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It was acknowledged that MLNs was a well-established prognostic factor for gastric carcinoma (Catarci et al 2011;Reis et al 2002). In many study, it had been demonstrated that the 7th UICC N stage was superior to the 5th/6th UICC N stage and Japanese N stage for prognostic prediction of gastric cancer by using Cox regression multivariate analysis (Deng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was acknowledged that MLNs was a well-established prognostic factor for gastric carcinoma (Catarci et al 2011;Reis et al 2002). In many study, it had been demonstrated that the 7th UICC N stage was superior to the 5th/6th UICC N stage and Japanese N stage for prognostic prediction of gastric cancer by using Cox regression multivariate analysis (Deng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As LN metastasis occurs during the early stages of this disease, regional lymphadenectomy is recommended as part of radical gastrectomy (Catarci et al 2011;Reis et al 2002).…”
Section: Backgroundsmentioning
confidence: 99%
“…Indication for DSG or TG and extent of lymph node dissection have been previously described [23, 24]. Reconstruction of digestive tract continuity after DSG consisted of a Roux-en-Y single-layer hand-sewn gastrojejunostomy and a Roux-en-Y stapled (25-mm circular stapler) esophagojejunostomy after TG.…”
Section: Methodsmentioning
confidence: 99%
“…Lymph node (LN) metastasis is the most common metastatic pattern of RGC, and regional lymphadenectomy is recommended as part of radical gastrectomy [8] , [9] . It was recently acknowledged that the total number of metastatic LNs is a more reliable prognostic indicator than positive anatomical lymphatic stations [10] .…”
Section: Introductionmentioning
confidence: 99%